2020
DOI: 10.1111/jdv.16306
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in 161 patients with mucosal melanoma: a study of German Central Malignant Melanoma Registry

Abstract: Background Mucosal melanoma is a rare malignancy which represents approximately 1% of all melanomas. It is shown that mucosal melanomas have a different biology and less favourable prognosis than its cutaneous counterpart. Objectives Predictive and prognostic factors of survival for mucosal melanoma have not yet been elucidated. The aim of this study was to investigate risk factors affecting the course of mucosal melanoma patients followed in our clinic. Methods One hundred and sixty‐one patients with mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
15
0
4
Order By: Relevance
“…On multivariate analysis, younger age, urban location of the patients and surgery were associated with better OS [52]. Other studies have found that age, tumor thickness, presence of ulceration, lymphovascular invasion, perineural invasion and tumor AJCC stage are the main predictors of survival [15,39,40].…”
Section: Prognostic Factorsmentioning
confidence: 89%
See 1 more Smart Citation
“…On multivariate analysis, younger age, urban location of the patients and surgery were associated with better OS [52]. Other studies have found that age, tumor thickness, presence of ulceration, lymphovascular invasion, perineural invasion and tumor AJCC stage are the main predictors of survival [15,39,40].…”
Section: Prognostic Factorsmentioning
confidence: 89%
“…The 5-year survival rate of colorectal melanoma ranges from 4.3% to 17.4% [73]. The median survival of AM has been reported as 21 months [95% CI: 11-30] [15]. The 5-year OS rates of Stage I, II and III are 26.7%, 9.8% and 0% respectively [35].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…The poor prognosis is likely a result of delay in diagnosis due to anatomic location. Overall survival (OS) has been cited to be highest in the vulvovaginal melanoma group, followed by sinonasal melanoma, and then anorectal melanoma [ 4 , 8 , 20 ]. Similar to findings reported in a series of 706 mucosal melanomas by Cui et al [ 6 ], no significant correlation between survival and anatomic sites is observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with prognosis, genetic alterations occurring in mucosal melanoma are different than those of cutaneous wild-type melanoma ( BRAF , NRAS and NF1 negative) [ 2 , 3 ]. The frequency of frequently mutated genes are as follows: NRAS (14–30%), BRAF (5–16%), NF1 (16%), KIT (5–15%), SF3B1 (12%), TP53 (8.9%), SPRED1 (7%), ATRX (6%) and CHD8 (4%) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Recently, IGF2R mutation was documented in 32% of 41 mucosal melanomas in comparison to 6% of 48 cutaneous melanomas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 45 , 46 Early reports of pervasive mortalities in elderly patients with comorbidities (8 out of 10) such as diabetes and heart and lung diseases underscored the apparent vulnerability of elderly individuals. 47 , 48 Other clinically significant comorbidities include but are not limited to chronic lung disease or moderate-to-severe asthma; serious heart conditions; immunosuppression, including cases of poorly controlled human immunodeficiency virus (HIV) or AIDS; prolonged use of corticosteroids; and severe obesity (body mass index ≥40). 49 During the course of the ongoing pandemic, several studies have focused on cohorts of COVID-19 patients who died from severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%